Plato, shame and politics - Olesiński, Dariusz (Folia Philosophica, 2011)
Recenzja książki Christiny H. Tarnopolskiej „Prudes, Perverts, and Tyrants: Plato’s «Gorgias» and the Politics of Shame”. Princeton: University Press, 2010.